Challenges, Regulations, and Strategies to Prevent Child Marriage in Indonesia: A Comparative Study with Malaysia - Busthomi Arifin; Rusmilawati Windari (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
Child marriage is a global issue that has become a challenge in many countries, one of which is Indonesia. The purpose of this research is to explore the factors of child marriage, analyze the child marriage regulations applied by Indonesia and then compare them with Malaysia in order to find the best ideal formulation for Indonesia in terms of regulating child marriage, and map out what steps need to be taken to reduce the number of child marriages. Included in the type of normative legal research by collecting all relevant legal materials through library research techniques and then analyzed descriptively qualitative. The results show that there are nine factors for child marriage ranging from poverty to self-will. In addition, there are differences in child marriage regulations in Indonesia and Malaysia where the positive thing that Indonesia can adopt from Malaysia is the synchronization of the age of the child in the Marriage Law and the Child Protection Law to be in line with the Convention on the Rights of the Child. Efforts to reduce the number of child marriages must have a strong synergy between the government and the community.